REMEDIBERBANTUANKOMPUTERSEBAGAIUPAYA UNTUK MENINGKATKAN PRESTASI BELAJAR FISlKA ZAT PADAT - Edi Istiyono (Jurnal Cakrawala Pendidikan, 2003)
The objectiveofresearch were: (I) to determine the influenceof remedial program by computer on the achievement of the SolidState Physics and (2)to determine the students self-learning in theremedial program by computer.Subjectof research was the student of the Study Program ofPhysics of Mathematics and Science Faculty in Yogyakarta- StateUniversity who took the Solid State Physics Subject. Data weregathered by meantof: (1) test and (2) observation. Test was used tocollect the students achievementin the Solid State Physics.By analyzing of data, it was concluded that: (1) remedialprogramby computer increases the learning achievement of theSolid State Physics and (2) the mostof students are self-learning inthe remedial programby computer